Emergency Telecommunications for Managing Disasters: A Complexity Science Perspective - Serrano-Santoyo, Arturo; Rojas-Mendizabal, Veronica (European Scientific Journal, ESJ, 2017)
Telecommunications technologies have shown great potential for humanitarian relief on a global scale. The complexity of the disaster scenario makes necessary to develop new strategies in order to respond efficiently and in a timely manner to humanitarian needs when disasters occur. Given the rapid technological advances and their associated convergence, we argue that the elements (subsystems) of a telecommunications system cannot be seen in an isolated manner, neither be conceptualized only as infrastructure; an interdisciplinary perspective is required. We suggest that a fragmented approach to telecommunications systems limits their application and effectiveness in disaster relief and recovery. In our approach, we consider the emergency telecommunications ecosystem as a socio-technical system. The understanding of the interactions of the main agents of such ecosystem is key to respond to disasters in a coordinated and orchestrated manner. Telecommunications technologies are important enablers, but should not be considered the center of the planning and execution stages of the disaster management process.